Exploring the Energy Consumption and Carbon Emissions Nexus in Nigeria - Udo, Emmanuel Samuel; Chiyem, Iyadi Rollins; Abner, Ishaku Prince; Ifeanyi, Onyemere; Okoh, Johnson Ifeanyi; Ajudua , Emmanuel Ifeanyi (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2025)
This study investigates the intricate nexus between energy consumption and environmental quality in Nigeria, a country that is highly vulnerable to climate change. Focusing on the Sustainable Development Goals (SDGs), particularly goal 13 climate action, this study examined the effect of diverse fossil fuel sources on environmental quality measured by CO2 emissions. By unbundling the diverse energy sources and assessing their individual and interactive influence from 1990 to 2023 using the Environmental Kuznets Curve (EKC) framework, this study provides a nuanced understanding of the impact of diverse energy sources on carbon emissions. By applying the EKC framework, this study aims to determine whether the nexus between economic growth and environmental degradation in Nigeria follows a hypothesized inverted U-shape. Using the Autoregressive Distributed Lag (ARDL) model, this study contributes to the extant literature by exploring both the long- and short-run linkages between energy consumption and CO2 emissions and analyzing the ripple effects across diverse economic sectors. The findings reveal a complex link between energy consumption, economic growth, and CO2 emissions, which is consistent with the EKC hypothesis. Energy consumption stimulates economic growth and significantly influences emissions from transportation, industrial activities, urbanization, and residential/commercial services in Nigeria. This study concludes with actionable policy recommendations emphasizing the transition to green energy, stringent emission regulations, and investment in public transportation infrastructure to mitigate CO2 emissions and enhance environmental quality. These insights can assist policymakers in formulating targeted interventions for sustainable growth and ecological sustainability.